PEMANFAATAN LIMBAH PECAHAN BETON SEBAGAI PENGGANTI AGREGAT KASAR PADA PERKERASAN ASPHALT - CONCRETE WEARING COURSE (AC-WC) - Rosyad, Farlin; Afrindo, Gaga (Ensiklopedia of Journal, 2023)
In the manufacture of asphalt mixture requires aggregate in large quantities. Because of the pavement structure consists of 90 – 95% aggregate. Of the one materials being used is gravel or coarse aggregate. Increased infrastructure development such as buildings, bridges, roads, and various other public facilities that use a lot of cocrete maerials can cause environmental dmage due to concrete waste that is not taken seriously. To limit the use of new aggregates from the nature, many recycling technologies for road pavement have been developed. The purpose of this study was to determine the effect concrete waste as a substitute for coarse aggregate in the laston mixture (AC – WC) for road pavement on the characteristic value of Marshall.This research uses marshall experimental and testing methods wit experiments and comparisons according to the levels of concrete waste variations as a substitute for  coarse aggregate of 0%%, 25%, 50%, 75% and 100% and variations in asphalt content 0f 6% according to the Bina Marga Specification (2018) revision 2.The results obtaines from this test produced the effect of marshall characteristics with an optimum asphalt content of 6% using optimum concrete waste 25% wich has a good effect on the marshall characteristic.